Theoretical and numerical study of composite repaired pipelines incorporating defect geometries - Deng, Meilin (2024)
With the development of pipelines transporting oil and gas, the number of pipelines suffering from corrosion and metal loss is also increasing. Composite repair technology has become an effective way to be widely used based on the current standards. However, current standards are considered conservative in determining the minimum composite repair thickness, and need to be optimized and improved. Therefore, this study aimed to put forward a new idea to improve the closed-form solution of composite repair thickness through numerical simulation and theoretical derivation, taking the defect sizes, property of putty and corroded pipe layer into consideration. Through response surface methodology, the design pressure (yield pressure, maximum allowable operating pressure and burst pressure) was determined by comparing to experimental results. Then, sensitivity analysis of defect sizes using response surface methodology and parametric study of defect sizes using finite element analysis were carried out. Finally, this study proposed a three-layer thin-walled model based on two assumptions, namely the same hoop strain of each layer and the same displacement of each layer. In the theoretical derivation process, the crucial step is the corroded pipe layer treated equivalently. The closed-form solutions of minimum composite repair thickness are then derived according to the composite stress and strain reaching the ultimate stress and the ultimate strain based on each assumption, respectively. Four closed-form solutions are obtained and validated with the experimental test and current repair design standards. Results revealed that the most influencing factor affecting failure pressure is the defect depth, with a recorded pressure difference of 15.3%. In contrast, defect length has a minimal effect, while defect width exerts a moderate impact, contributing to pressure differences of 0.1% and 1.2%, respectively. Besides, results from theoretical derivation show that the most accurate close-form solution is based on assumption 2 with only 0.3 % error margin. The accuracy of comparison also reveals that the proposed closed-form solution outperforms the current standards. The result of this study is significant as it could make the composite repair more cost-effective and assist maintenance engineers in better evaluating the reliability of pipeline rehabilitation. Meanwhile, this study also provides a theoretical basis for the revision of the current standards.